The Idea of "Depth" in Ignatian Pedagogy in Face of some Tendencies of Digital Education - Rastislav Nemec (Jesuit University Ignatianum in Krakow, 2021)
RESEARCH OBJECTIVE: The aim of this study is to present some contradictory tendencies and  draw attention to two phenomena that  prove their contradiction. The first one is the missing dimension of depth of knowledge which suggests that the ubiquitous source of information and student awareness is not automatically a qualitative asset. On the other hand, the gradual digitalization of education increasingly indicates the fragmentation of such a teaching process. THE RESEARCH PROBLEM AND METHODS: The article intends to emphasize the importance of two pillars of Jesuit pedagogy, which historically date back to the Spiritual Exercises of St. Ignatius and which were revived by the interpretations of two former superiors of the Society of Jesus, P. Arrupe and A. Nicholas. However, the present times seems to bring different  goals in the perspective of digital media and professional profiling of the student. THE PROCESS OF ARGUMENTATION: The article is structured as follows. In the first part, the author presents the conclusions resulting from  research and measurements conducted in Slovakia in recent years, which aimed at examining  students' skills in reading comprehension and indicates the  growing support for the digitalisation of education in Slovakia, which the author (and not only he) perceives as highly contradictory. On the other hand, the article makes an attempt to counter  the notions: the "reference to depth" and the integrity of the human being, more and more often mentioned in the literature.  RESEARCH RESULTS: The present study is to demonstrate that Jesuit pedagogical appeal to the need for "integral" development of the person and "depth" is extremely actual in this field. CONCLUSIONS, INNOVATIONS, RECOMMENDATIONS: The aim of the study is to show the need to re-develop these threads of depth and integral development of the human being, along with other pillars of Jesuit education, and  rethink its message.